2004
DOI: 10.1002/eji.200324711
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of membrane molecules from T cells endows antigen‐presenting cells with novel functional properties

Abstract: Although intercellular transfer of cell surface molecules has been observed between several cells of the immune system, the physiological relevance of this phenomenon remained obscure. Until now the transfer of molecules between antigen-presenting cells (APC) and T cells has been described as a unidirectional process from APC to T cells. However, here we show that T cells in turn donate molecules to APC, and that T cell-derived vesicles can mediate this transfer. The transferred proteins are incorporated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 40 publications
1
41
0
Order By: Relevance
“…Intercellular transfer of proteins from T cells to APCs might also balance the immune responses, as anergic or regulatory T-cell-derived vesicles have been shown to induce a tolerogenic phenotype in APCs (95). It was shown that CD8 + T cells which had acquired cognate pMHC I complexes became susceptible to antigen-specific lysis or fratricide killings, thereby contributed to effector clearance (18,23,96).…”
Section: Suppressive Effect On Immune Responsesmentioning
confidence: 99%
“…Intercellular transfer of proteins from T cells to APCs might also balance the immune responses, as anergic or regulatory T-cell-derived vesicles have been shown to induce a tolerogenic phenotype in APCs (95). It was shown that CD8 + T cells which had acquired cognate pMHC I complexes became susceptible to antigen-specific lysis or fratricide killings, thereby contributed to effector clearance (18,23,96).…”
Section: Suppressive Effect On Immune Responsesmentioning
confidence: 99%
“…32 Activated T cells can also secrete bioactive EXO, [8][9][10] which can be taken up by DCs or B cells via direct intercellular molecule transfer from T cells to APCs. 11 However, the potential effect of T-cell EXO on the regulation of immune responses is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, T-cell EXO can be taken up by DCs or B cells by intercellular molecule transfer from T cells to antigen-presenting cells (APCs), leading to modulation of the APC and regulation of Tcell responses. 11 However, the potential effect of activated T-cell EXO on modulation of DC-induced immune responses is still largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that DCs can uptake T cell EXOs (15). To assess T cell EXO uptake by DCs, DC OVA were incubated with CFSE-EXO for 4 h and then analyzed by flow cytometry and confocal fluorescence microscopy.…”
Section: Uptake T Cell Exo Via Pmhc I-tcr and Cd54-lfa-1 Interactionsmentioning
confidence: 99%
“…In addition, these active T cells also secrete bioactive EXOs, which express TCRs and Fas ligand (FasL) (13,14) and can be taken up by APCs or B cells via direct cultivation (15). It has also been demonstrated that these FasLexpressing T cell EXOs induced apoptosis formation of the bystander T cells with unknown mechanism (16).…”
mentioning
confidence: 99%